Environmental and economic performances of municipal solid waste incineration fly ash low-temperature utilization: An integrated hybrid life cycle assessment. (15th March 2022) - Zheng, Rufeng; Wang, Yao; Liu, Zixing; Zhou, Jizhi; Yue, Yang; Qian, Guangren
Abstract: Detoxification and utilization of municipal solid waste incineration fly ash (MSWIFA) with low temperature pretreatment, low environmental burden and low cost have become more and more popular topics in the world. Based on integrated hybrid life cycle assessment, this study compares the environmental and economic performance of MSWIFA low-temperature utilization with the cement kiln co-processing technique when the scenarios with or without salt recovery were considered. The result shows that the hybrid integrated life cycle assessment captures larger environmental and economic benefits of MSWIFA utilization than traditional method due to extending the system boundary to the entire economy. Especially, the avoiding in global warming, primary energy demand and human toxicity from the economic input-output system account for 15%–53%, 26%–65%, and 93%–96% of total impacts, respectively. Additionally, the hybrid model captures a considerable avoidance of cost for MSWIFA treatment. When adopting salt recovery, except for human toxicity, the environmental credit of low-temperature utilization is 3.19–12.64 times higher than that of cement kiln co-processing. Moreover, because of the saving of chemicals and energy, the environmental and economic credit of scenarios without salt recovery is significantly higher than that of scenarios with salt recovery. Findings of this study provide scientific foundations to promote the low-temperature utilization of MSWIFA, as well as multiple solutions on ash-washing wastewater treatment. Highlights: Apply IHLCA to evaluate low-temperature MSWIFA utilization for the first time. Low-temperature MSWIFA utilization performs better than the cement kiln co-processing in environment. Salt recovery from ash-washing wastewater is inferior to discharging to ocean. Provide multiple solutions for ash-washing wastewater treatment.